Social Obligations of Forestry Sector-vis-a-vis Forestry Management Planning - Chowdhary, R. L. (Indian Forester, 1977)
The Report of the Working Group on Forests (19721) have identified three important obligations for Forestry Sector for the Fifth Five Year Plan, namely, the important links between forests and food, forests and people and forests and wood. The National Commission on Agriculture (1972) has also stressed the need for reorienting our present day conservation oriented forestry management objectives, towards a more dynamic and growth oriented forestry, which would be in harmony with the general objectives of regional and national economic development. Woefully enough, the present day working plan documents have very short sighted policy goals. Very often, these lack the necessary data base to help in formulation and implementation of intensive forestry management programme, which would be in consonance with the rapidly changing requirements of the country. It is, therefore, necessary to enlarge the scope of data base in a traditional working plan and include critical assessment of resources, demand and supply of forest products. wood balances, and various management alternatives open to the managers of the resources, so that the Forestry Sector can occupy its rightful place in the national main stream of development planning.